THE IMPACT OF E-COMMERCE ON INDONESIA ECONOMIC GROWTH: INTERMEDIATION MODELS WITH FINANCIAL TECHNOLOGY CONSTRAINT - Nopiah, Ririn; Ekaputri, Retno Agustina; Barika, Barika; Febriani, Ratu Eva (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
The COVID-19 pandemic triggered economic shocks that adversely affected the global economy. Economic growth contracted significantly. Restrictions on economic activity trigger people's shopping behavior to switch to non-cash and online systems. E-commerce, as one part of digital economic transformation, has experienced a significant increase which impacts the flow of dissemination of ideas, innovations, and information, thus encouraging economic growth. This study analyzes the Impact of e-commerce on economic growth in Indonesia during the COVID-19 pandemic using intermediation models and fixed effect analysis. The results show that e-commerce negatively and significantly impacts economic growth during 2019 and 2021. Because e-commerce stimulates economic growth in a country but needs to be supported by quality infrastructure, quality broadband internet, online security (cyber security), and digital payment systems (e-payment). The variables of online financing, efficiency of government spending, length of schooling, and number of tourists have a positive and significant effect. Meanwhile, the poverty rate and human development index have a negative and significant effect. In maximizing e-commerce activities in Indonesia, strong support and collaboration from the government, financial institutions, and the Ministry of Communication and information technology are needed.